Two conformational polymorphs of a bioactive pyrazolo[3,4-d]pyrimidine - Tan, Sang Loon *; Tan, Yee Seng *; Ng, Jia Hui; Dolzhenko, Anton V; Tiekink, Edward R. T. * (MDPI, 2023)
Two monoclinic (P21/c; Z′ = 1) polymorphs, α (from methanol) and β (from ethanol, n-propanol and iso-propanol), of a bioactive pyrazolo[3,4-d]pyrimidine derivative have been isolated and characterised by X-ray crystallography as well as by a range of computational chemistry techniques. The different conformations observed for the molecules in the crystals are due to the dictates of molecular packing as revealed by geometry-optimisation calculations. The crucial difference in the molecular packing pertains to the formation of phenylamino-N–H···N(pyrazolyl) hydrogen bonding within supramolecular chains with either helical (α-form; 21-screw symmetry) or zigzag (β-form; glide symmetry). As a consequence, the molecular packing is quite distinct in the polymorphs. Lattice energy calculations indicate the β-form is more stable by 11 kJ/mol than the α-form.